2019
DOI: 10.3390/agronomy9110686
|View full text |Cite
|
Sign up to set email alerts
|

A Model-Based Real-Time Decision Support System for Irrigation Scheduling to Improve Water Productivity

Abstract: A precisely timed irrigation schedule to match crop water demand is vital to improving water use efficiency in arid farmland. In this study, a real-time irrigation-scheduling infrastructure, Decision Support System for Irrigation Scheduling (DSSIS), based on water stresses predicted by an agro-hydrological model, was constructed and evaluated. The DSSIS employed the Root Zone Water Quality Model (RZWQM2) to predict crop water stresses and soil water content, which were used to trigger irrigation and calculate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 47 publications
4
19
0
Order By: Relevance
“…The soil moisture content is used to describe the water status in the uppermost part of a field soil [6]. The determination of soil moisture status has been considered regarding plant-water relations [7], while the climatic data are considered to perform a model-based real-time decision support system for irrigation systems together with the soil moisture status, such as air temperature, air humidity, solar radiation, and wind speed [8]. Furthermore, the smart watering system was developed for irrigation scheduling based on Block-chain and fuzzy logic approach by employing economical sensor devices [9].…”
Section: Introductionmentioning
confidence: 99%
“…The soil moisture content is used to describe the water status in the uppermost part of a field soil [6]. The determination of soil moisture status has been considered regarding plant-water relations [7], while the climatic data are considered to perform a model-based real-time decision support system for irrigation systems together with the soil moisture status, such as air temperature, air humidity, solar radiation, and wind speed [8]. Furthermore, the smart watering system was developed for irrigation scheduling based on Block-chain and fuzzy logic approach by employing economical sensor devices [9].…”
Section: Introductionmentioning
confidence: 99%
“…In their studies, Chen et al (2019) highlighted that a precisely timed irrigation program to meet crop water demand is vital to improving water use efficiency in arid farmlands. A real-time irrigation planning infrastructure was created, and DSS was developed for irrigation planning [26]. Bomsdorf and Derigs (2008) developed a model to solve the filmmaking planning problem in their work.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Results from the SWAT model, which was calibrated using remotely sensed (RS) evapotranspiration data before being implemented for BMP scenario evaluation, demonstrate the efficacy of the tool to inform watershed managers of the potential benefits of various BMP scenarios in reducing sediment yield and N/P loads to streams. Chen and coauthors [13] evaluated a real-time decision support system for irrigation scheduling (DSSIS) which was built with an agro-hydrological model. When applied to a cotton field, the authors found that the DSSIS performed better than other methods that were evaluated concurrently.…”
Section: Csms As a Decision Toolmentioning
confidence: 99%